2008
DOI: 10.4049/jimmunol.180.11.7349
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Calmette-Guérin and TLR4 Agonist Prevent Cardiovascular Hypertrophy and Fibrosis by Regulating Immune Microenvironment

Abstract: Hypertension-induced cardiovascular hypertrophy and fibrosis are critical in the development of heart failure. The activity of TLRs has been found to be involved in the development of pressure overload-induced myocardial hypertrophy and cardiac fibrosis. We wondered whether vaccine bacillus Calmette-Guérin (BCG), which activated TLR4 to elicit immune responses, modulated the pressure overload-stimulated cardiovascular hypertrophy and cardiac fibrosis in the murine models of abdominal aortic constriction (AAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…Although a number of studies have highlighted the differential regulatory roles for Th1 and Th2 responses in the pathogenesis of tissue fibrosis (15,31), it is unclear how the Th1/2 balance affects the progression of tissue fibrosis. Recent studies have indicated that autophagy acts as an immune effector mechanism against intracellular pathogens and functions to heal injured tissue and remove cellular debris.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of studies have highlighted the differential regulatory roles for Th1 and Th2 responses in the pathogenesis of tissue fibrosis (15,31), it is unclear how the Th1/2 balance affects the progression of tissue fibrosis. Recent studies have indicated that autophagy acts as an immune effector mechanism against intracellular pathogens and functions to heal injured tissue and remove cellular debris.…”
Section: Discussionmentioning
confidence: 99%
“…39 It has been shown that LPS and CysLT induce the activation of ERK1/2 and p38. 41,42 Taking this into account, we decided to analyse the activation of ERK1/2 and p38 MAPK. Western blots of lysates from DCs cultured without or with LPS (1 lg/ml) for 30 min at 37°w ere incubated in the presence or not of LTC 4 (10 -8…”
Section: Leukotriene C 4 Activates Mapk Depending On the Activation Smentioning
confidence: 99%
“…Human breast or colon cancer tissue microarray slides (US Biomax) were detected as previously described (27).…”
Section: Tissue Microarray Slides and Immunohistochemistrymentioning
confidence: 99%